Optimization of Nile Tilapia (Oreochromis Niloticus) Production in Floating Net Cages Through Feed Engineering to Support Food Security in The Fisheries Sector - Lutfiani, Cindi; Rakhmawati, Rakhmawati; Indariyanti, Nur (Indonesian Journal of Multidisciplinary Science, 2026)
National food security demands the availability of sustainable sources of animal protein, one of which is through increasing the production of tilapia (Oreochromis niloticus). As a strategic fishery commodity, tilapia has rapid growth, high economic value, and wide adaptability, including in the floating net cage system (KJA) in salinity waters. However, the high cost of feed, especially from the protein content, is still a major obstacle in cultivation. Efficiency efforts can be made through the formulation of lower protein feeds with the addition of chromium yeast (Cr-yeast) which plays a role in increasing insulin sensitivity and improving glucose and lipid metabolism. This study aims to examine the effect of variation in feed protein levels (28% and 34%) and Cr-yeast supplementation on the growth performance and biochemical profile of tilapia blood in KJA. The parameters observed included survival rate (SR), absolute weight growth, daily growth rate, feed conversion (FCR), feed efficiency, protein retention, fat retention, as well as blood biochemical indicators (blood glucose, triglycerides, cholesterol, HDL, and LDL). The results showed that low-protein feed (28%) was still able to support the rate of survival, growth, and feed efficiency, which is comparable to high-protein feed (34%). The addition of Cr-yeast to feed 28% has been proven to increase the efficiency of energy metabolism through the protein sparing effect mechanism, which is a condition when energy needs are met more by lipids so that proteins can be directed to tissue formation.